SMALL IS BEAUTIFUL - Khudabux, Imteyaz (SCHOOL SCIENCE, 2011)
When UNESCO first launched its global microscience project 15 years ago, many countries still took a purely theoretical approach to science teaching, not out of choice but of necessity. They simply could not afford the exorbitant cost of equipping schools and universities with laboratories. The miniature kits proposed by UNESCO offered a low-cost, safe alternative for experimentation. Given their multiple advantages, it was not long before the miniature kits caught on. Cameroon, Tanzania and South Africa have invested massively in them, as have Russia and the U.K., Angola, Ethiopia,Namibia, Malaysia, Sudan, the Gambia and the Palestinian Authority have all held workshops to adapt the kits to the national curriculum, while other countries are still at the stage of demonstration workshops. Today, there is a growing demand for UNESCO’s assistance in customising the miniature kits for national use — and nowhere more so than in Africa.